Lichen striatus with onychodystrophy on a finger. Case report - Omulecki, Anastazy; Kot, Marek; Woźniacka, Anna (Dermatology Review/Przegląd Dermatologiczny, 2016)
Introduction . Lichen striatus (LS) is a benign, self-limited, inflammatory dermatosis of unknown etiology, which mainly affects children. It manifests as flat brownish papules with linear distribution. Most often they are located on the extremities. In rare cases lesions are located on a finger and then nail dystrophy can occur. Objective . To describe a rare case of LS with nail involvement. Case report. A 10-year-old girl demonstrated a linear plaque of confluent brownish papules on the dorsal surface of the second right hand finger with accompanying onychodystrophy. Conclusions . Lichen striatus can be the cause of dystrophic changes of nails. Than it is necessity to differentiate it with dermatophytosis and dermatoses of linear configuration.